Potensi Hasil dan Mutu Beras Sepuluh Galur Harapan Padi untuk Lahan Rawa Pasang Surut - Hairmansis, Aris; Aswidinnoor, Hajrial; Supartopo, ,; SuwarnoSuwarno, Willy Bayuardi; Suprihatno, Bambang; Suwarno, , (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2013)
Breeding programs to improve rice varieties for tidal swamp areas have successfully developed a number of promisingbreeding lines. The objectives of this study were to evaluate the performance of ten advance breeding lines in multilocationyield trials and to analyze grain quality of the lines. The lines and two check rice varieties, IR42 and Batanghari, wereevaluated in replicated yield trials in six different tidal swamp environments. Grain quality of these lines were analyzed todetermine physical and chemical properties of the milled and cooked rice. Result from multilocation yield trials showedthat the breeding lines had higher yield potential compared to popular variety IR42 and their yields were comparable tothe control variety Batanghari. The lines showed different adaptability against different environments; some of the linesdemonstrated wide adaptability while the others showed specific adaptation ability. All of the lines had good grain qualitywhile they had different shape and texture which made them potential to be accepted in different regions. The result fromthis study indicated that all of the lines have potential to be commercially cultivated in tidal swamp areas. In addition, dataobtained from this study have been used in the registration of three lines as new varieties for swampy area namely IPB 1RDadahup, IPB 2R Bakumpai and Inpara 6.Keywords: adaptation, grain quality, multilocation trials